2021
DOI: 10.24090/komunika.v15i1.4493
|View full text |Cite
|
Sign up to set email alerts
|

Da’wa Critical Discourse Analysis in the Omar and Hana Cartoon Film on “Alalala Raju” Episode

Abstract: Cartoons, which are closely associated with children, tend to contain violence and mere entertainment. It is still rare to find comics that have Islamic values. This study aims to critically analyse the construction of Islamic values in the cartoon film Omar and Hana episode Alalala Raju. The research was qualitative research using the Van Dijk model of critical discourse analysis and content analysis of the da’wa message. The data was from a YouTube channel called Omar & Hana - Islamic Children’s Songs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…Turkman proposed Investigating The Responses of Children to Animated Films that They View in 2021 to assess the degree of correctness of children's responses to the content of the animated films they watch. Utami and Harianto (2021) in their study titled Da'wa Critical Discourse Analysis in the Omar and Hana Cartoon Film on "Alalala Raju" Episode found that the structure of the film's text contains a discourse of advice to children to share objects they have and love. Naji and Abbas (2022) conducted a study entitled Self-society Conflict in Angie Thimas' The Hate U Give: A Critical Discourse Analysis.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Turkman proposed Investigating The Responses of Children to Animated Films that They View in 2021 to assess the degree of correctness of children's responses to the content of the animated films they watch. Utami and Harianto (2021) in their study titled Da'wa Critical Discourse Analysis in the Omar and Hana Cartoon Film on "Alalala Raju" Episode found that the structure of the film's text contains a discourse of advice to children to share objects they have and love. Naji and Abbas (2022) conducted a study entitled Self-society Conflict in Angie Thimas' The Hate U Give: A Critical Discourse Analysis.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In a study conducted by Lillard and Peterson (2011), it was discovered that 4-year-old children's executive function was negatively impacted after only 9 minutes of watching a fast-paced television program. Utami and Harianto (2021) found that the structure of the film's text contains a discourse of advice to children to share objects they have and love. Owing to the indisputable fact that technology has advanced, Disney and its products are dominant.…”
Section: Introductionmentioning
confidence: 99%